Occurrence of Neophilopterus Tricolor (Burmeister, 1838) on a Black Stork (Ciconia Nigra) in the Kızılırmak Delta, Turkey - Açıcı, Mustafa; Eren, Gökhan; Özkoç, Ömral Ünsal; Öztürk, Mehmet; Bölükbaş, Cenk Soner; Açıcı, M.; Eren, G.; Özkoç, Ö.Ü.; Ozturk, M.; Bölükbaş, C.S. (Chartered Inst. of Building Services Engineers, 2021)
A dead black stork (Ciconia nigra) was found by an a birdwatcher in the Kızılırmak Delta near Samsun, Turkey and brought to the Parasitology Laboratory of the Faculty of Veterinary Medicine at Ondokuz Mayis University for ectoparasitological examination in December 2019. During the examination, 45 specimens of chewing lice (21 males, 18 females and 6 nymphs) were collected. All of the specimens were identified as Neophilopterus tricolor (Burmeister, 1838) (Ischnocera: Philopteridae). Neophilopterus tricolor is reported from the black stork (C. nigra) for the first time in Turkey. © 2021, Chartered Inst. of Building Services Engineers. All rights reserved.
Türkiye’de Kızılırmak Deltası’nda, Bir Kara Leylekte (Ciconia Nigra) Neophilopterus Tricolor (Burmeister, 1838) Olgusu
SCI-Expanded
Q4
Keywords: Black Stork; Ciconia Nigra; Neophilopterus Tricolor; Philopteridae; Phthiraptera; Veterinary Sciences